Investigating the Mediating Role of Cybersecurity Awareness in Bridging Cognitive Factors and Secure Behavioural Intentions: A Quantitative Approach Using PLS-SEM - Muhammad Agreindra Helmiawan; Yanyan Sofiyan; Esa Firmansyah; Dody Herdiana; Irfan Fadil; Titik Khawa Abdul Rahman (Jurnal Teknik Informatika (Jutif), 2026)
Cybersecurity threats have become increasingly sophisticated, rendering the human element a critical vulnerability despite advanced technical safeguards. This study investigates the cognitive drivers of cybersecurity awareness and secure behaviour through the lens of Protection Motivation Theory (PMT), specifically examining the mediating role of Cybersecurity Awareness (CA). A quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to analyse data from students and faculty members in a higher education setting. The findings substantiate that Self-Efficacy (β=0.412,p<0.05) and Response Efficacy (β=0.385,p<0.05) are significant predictors of CA, with the model achieving a robust R2 value of 0.703. Crucially, the mediation analysis identifies CA as a vital cognitive bridge that translates internal confidence into Secure Behavioural Intentions. These results offer an integrated framework for developing targeted intervention strategies in academic institutions. For the field of Informatics, this research underscores the urgency of designing human-centric security systems that prioritize psychological empowerment to foster sustainable digital resilience against an evolving threat landscape.